Peningkatan Kemampuan English for Tourism bagi Pemuda Desa Karang Bongkot untuk Menghadapi Program the Best Halal Tourism Nusa Tenggara Barat - Arifin, Muhamad; Abrar, Abrar; Supriyadi, Supriyadi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2024)
This community service activity focuses on enhancing the English language skills of youth, particularly in the context of English for Tourism, with the aim of increasing their competitiveness in the local job market, especially in the tourism sector. This research employs a descriptive qualitative method with a participatory action research approach. Data were collected through observations, interviews, and questionnaires completed by training participants. Data analysis was conducted qualitatively to assess the effectiveness of the teaching methods and their impact on participants' English skills. The study's findings outline the following steps: 1) Planning, which includes: (a) setting goals and objectives, (b) selecting methods and strategies, and (c) preparing a work plan. 2) Implementation, which combines conceptual learning and field practice, including: (a) structured English courses covering basic conversations, tourism terminology, and practical situations in tourism jobs, and (b) field practice through simulations and hands-on activities at local tourist sites. 3) Evaluation conducted weekly and at the end of the program, to measure achievements and provide notes and recommendations for similar future activities. For follow-up, it is recommended to conduct regular meetings, assign competent PkM students, and optimize campus support by establishing an English language course institution. This program aims not only to improve the English skills of youth but also to support local economic development through the tourism sector and related industries.